2010
DOI: 10.1007/s00436-010-1875-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacterial metabolites on microsporidian Nosema ceranae and on its host Apis mellifera

Abstract: Nosemosis, a disease caused by a microsporidian infection, is one of the most frequently observed parasitic pathologies affecting adult honeybees. Presently, Nosema ceranae seems to be the main microsporidian infection in Apis mellifera. The antibiotic fumagillin is the only compound available to treat Nosema diseases; however, it is no longer licensed in most EU member states; therefore, the need to identify new molecules/substances prevails. The intent of this paper is to test bacterial metabolites by Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 35 publications
(32 reference statements)
3
55
0
1
Order By: Relevance
“…In the same way, Corby-Harris et al (2016) discovered an increased resistance to Nosema infection by bees fed a hive bacterium. Concerning bacterial metabolites, Porrini et al (2010) suggested that a surfactin could damage the spore external structure decreasing their viability. Maggi et al (2013) as well proposed a hypothesis about the alteration of microsporidium envelope by an organic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, Corby-Harris et al (2016) discovered an increased resistance to Nosema infection by bees fed a hive bacterium. Concerning bacterial metabolites, Porrini et al (2010) suggested that a surfactin could damage the spore external structure decreasing their viability. Maggi et al (2013) as well proposed a hypothesis about the alteration of microsporidium envelope by an organic acid.…”
Section: Discussionmentioning
confidence: 99%
“…strain culture (Sabaté et al, 2012) or metabolic products of specific Bacillus spp. (Porrini et al, 2010) and Lactobacillus spp. (Maggi et al, 2013) were administered to bees.…”
Section: Introductionmentioning
confidence: 99%
“…It should further be noted that the use of Fumagillin is not yet permitted in the majority of the member states of the European Union due to the high concentration of drug residues in the honey , Porrini et al 2010. A medication needs to be found which does not contaminate the honey, and especially does not affect the health of consumers.…”
Section: Control Methodsmentioning
confidence: 99%
“…A medication needs to be found which does not contaminate the honey, and especially does not affect the health of consumers. In this situation, Porrini et al (2010) suggests the use of bacterial metabolites produced by bacteria such as Bacillus and Entorococcus isolated from the mid intestine of the honey bee and from its honey. One possibility is surfactin (a compound produced by B. subtilis), which significantly suppresses the parasite load and does not damage the health of the bee.…”
Section: Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation